Agrotechnoparks development: experience and perspectives - T. N. Polutina (Высшее образование в России)
The experience in creating the regional agrotechnoparks and the specifics of their activity in the framework of higher professional educational institution are considered. Also it isnoted the necessity of state participation and influence on the processes of agrarian science development and innovative activity.